CASE REPORT: ANATOMICAL PATOLOGY AND HISTOPATHOLOGICAL STUDY OF LANDRACE WHICH HOG CHOLERA AND HELMINTHIASIS INFECTION - Dharmayanti, Ayu Diah (Buletin Veteriner Udayana, 2022)
Necropcy on landrace pigs with the protocol 142/N/18 is to know the changes of pathologyanatomy and histopathological findings. Clinical signs were observed was languid, breathless, convulsions, diarrhea, and paralyzed. 3.5 months pig landrace were necropted and the sample organs with pathological changes were taken and fixed using Neutral Buffered Formalin (NBF) 10%. The organ sample were brain, trachea, esophagus, lungs, heart, liver, spleen, kidney, pancreas, small intestine, caecum, and large intestine. All of the organs that observed were cut into small size 1 x 1 x 1 cm, then fixed through rinse into Neutral Buffer Formalin (NBF) 10% for 24 hours. Histophatological preparations was made using Hematoxylin-Eosin colouration. Based on clinical symptoms, changes in anatomical pathology, and histopathology the pig landrace were infected with Hog Cholera and Helminthiasis .